Evaluation of motorcycle seat with lumbar support massager in reducing discomfort and maintaining spinal posture among traffic police riders - Mohammad Yusof, Nur Athirah Diyana (2021)
Traffic police riders are exposed to prolonged static postures causing significant angular deviation of the musculoskeletal, including the lumbar angle (L1-L5). This postural alteration contributes to muscle discomfort, especially in the lower back area, as it is one of the most severe modern diseases nowadays. Discomfort due to riding a motorcycle is an issue that needs to be addressed as it has long-term effects of musculoskeletal disorders (MSD) on motorcycle riders, especially among occupational groups. Thus, this study aims to evaluate lumbar support with a built-in massager system in order to reduce discomfort among traffic police riders. The first stage of this research examines the ergonomic problems experienced by the riders using a valid motorcycle seat discomfort survey, body chart discomfort, extensive literature search and prior patent search. The data from this stage was then analysed and used as input in the second stage for product design specification (PDS) to develop a motorcycle seat prototype. A total of 18 criteria of PDS were chosen for the development of the prototype. In the third stage, an experimental study was conducted among 24 traffic police riders (12 participants each in the control and experimental groups) using an existing motorcycle seat and a developed motorcycle seat prototype. Each participant was required to wear a TruPosture smart shirt (to monitor spinal angle posture) while riding a motorcycle for 20 minutes. The seating and body regions discomfort was assessed using a 100-millimetre Visual Analogue Scale (VAS) after the ride. As a result, the experimental group recorded a reduced discomfort and maintained and improved the spinal posture during the ride duration compared to the control group. From the analysis, there was a statistically significant difference (seat length, vibration, physical design, tendency to slide, the pressure under buttocks, with/without lumbar support, and with/without massager system) between the pre-test and post-test in the experimental group (p<0.05). Seven body regions showed a statistically significant difference in the pre-test and post-test in the experimental group, namely the neck, shoulders, hand, upper back, lower back, buttocks, thighs and calf (p<0.05). There was also a statistically significant difference in all sensors at the 0th, 10th, and 20th minutes between the pre-test and post-test in the experimental group (p<0.05). The application of a lumbar support with a built-in massager system showed a lower angle deviation compared to the control group. Overall, the seat discomfort was reduced by 17.0% to 67% and the muscle discomfort was reduced by 15.0% to 63.0% after 20 minutes of using the prototype. As a conclusion, the motorcycle seat intervention helps reduce traffic police riders’ discomfort during prolonged vehicle usage as well as support body posture, and therefore, has the potential to reduce the risk of developing MSD and spinal injury from this occupational work task.